Liberia Rapid Social Assessment - World Bank (World Bank, Washington, DC, 2012)
This note summarizes the main findings of the Rapid Social Assessment (RSA) Update. To respond to community tensions and to build upon emergent positive social relations the Update recommended a new impetus for local and community development in Liberia. Community Driven Development (CDD) operations are an appropriate way to foster cohesion at the local level but the RSA Update suggests that they still need to provide more attention to the following key areas at the local level: i) Improving representation and participation in local and community development processes; ii) Working within emerging local governance structures; iii) Strengthening coordination of local and community development.